Assessing students’ morphological awareness on the use of affixation at English education study program - Putri Endah Karunia; Mabaroh, Barotun; Pusparini, Diah Anita (Journal of English Language Proficiency, 2025)
This research employed a descriptive qualitative method. The participants were 16 students from the even semester students’ of morphological awareness class 2022 in the academic year 2023/2024 who joined English Morphology subject at English Education Study Program of Universitas PGRI Wiranegara. This research was done by researcher on 15th May, 2024. The data collection methods included a morphological awareness test and interviews. The overall score of the morphological awareness test was 52.75 which consisted of 50 words affirmation of affixation, 21 of them used prefixes and 29 used suffixes which meant class 2022 of academic year 2023/2024 at English Education Study Program were in the average category. The following data portion of the students, specifically 43.75%, demonstrated average proficiency in using prefixes and suffixes. In contrast, 37.5% of the students showed good proficiency. However, 18.75% of the students were categorized as below average. The interviews revealed that the students struggled with identifying and analyzing word formation of affixation by using prefixes and suffixes. The researcher concludes that the students’ morphological awareness on the use of affixation needs improvement. The researcher suggests for the future researchers to conduct similar research with different types of analytical strategies and method for morphological awareness.